Composition of Volatile Compounds Generated from Simulated Thermal Reaction of L-Theanine with Monosaccharides - GUO Xiangyang, WAN Xiaochun (Shipin Kexue)
To investigate the potential of L-theanine (Thea) as an aroma precursor, the composition of volatile compounds generated from the thermal reaction between Thea and monosaccharides, simulating the Maillard reaction, was analyzed by gas chromatography-mass spectrometry (GC-MS). Thea reacted with four common monosaccharide in tea, D-glucose (Glc), D-galactose (Gal), D-arabinose (Arab) and D-xylose (Xyl) at 120 ℃ for 2 h, generating volatile compounds. The reaction with Glc and Gal generated larger numbers of volatile compounds (32 and 21, respectively), and 17 and 12 nitrogen-containing compounds were found in the reaction products, respectively, heterocyclic compounds with pyrrole and amide structures being the major ones, including four compounds contributing to roasted aroma, 4-ethyl-2-methylpyrrole, 4-ethyl-2,3-dimethyl-1H-pyrrole, 2-acetylpyrrole and N-ethyl succinimide. In contrast, only 6 and 9 volatile compounds were identified in the reaction products of Thea with Arab and Xyl, respectively. The reaction with Arab produced larger amounts of heterocyclic compounds with pyrrole structure such as 2,3-dimethyl-1H-pyrrole, responsible for roasted aroma, whereas the reaction with Xyl mainly produced heterocyclic compounds with furan structure. Additionally, Thea was transformed into volatile components when heated to 120 ℃. Among the identified volatile compounds, those with pyrimidine structure and alkane compounds were present in higher amounts. Furthermore, it was speculated that some volatile components might be formed by the Maillard reaction or the Strecker degradation. Principal component analysis (PCA) could effectively distinguish different thermal reactions, indicating that the reaction characteristics of Thea with different monosaccharides varied. This study not only provides data support for understanding the formation mechanism of tea aroma but also lays a theoretical foundation for the processing optimization and quality control of tea.